Geoheritage Values of the Wairarapa “Mudstone Country”, North Island, New Zealand - Julie Palmer; Karoly Nemeth; Alan Palmer; Szabolcs Kosik (Geoconservation Research)
The Manawatu and Wairarapa regions, lower North Island, are an important geological archive for New Zealand but are not among the iconic geotourism attractions of New Zealand. Recently the geoheritage values of the region have been discussed by various groups including Massey University and Horizons Regional Council with an aim to promote the region to visitors seeking destinations with geological significance. The suggestion has been made the Manawatu River form the backbone of a geopark. While Manawatu River is regionally significant, we argue it lacks the unique attributes needed for globally significant geoheritage value. Here we demonstrate the wider region has at least two globally unique and geologically superb features that should be evaluated using global comparative studies. Exceptional turbidite successions representing accretionary prism successions are exposed in the Wairarapa region. These are comparable to the iconic “flysch” locations of the North American Cordillera, the Alps, the Pyrenees and the Carpathians. Furthermore, a succession of thrust faults and related mélange sequences are among the best exposed and most accessible in New Zealand. These undoubtedly carry high geoheritage value and we propose that these two geological features, with community support, regional council funding and the local university (Massey) facilitating the transfer of knowledge to the community, should be signposted and promoted to visitors. In the long term the stunning geological succession of the Wairarapa Mudstone Country should gain international recognition and form the basis of a UNESCO Global Geopark.